Method for modifying surface of high-voltage layered oxide positive electrode material
By quenching the reducing solution on the high-pressure laminated oxide positive electrode material and adjusting its surface structure, the problems of complex and poor versatility in the existing technology are solved, and the efficient surface modification of the material and the significant improvement of the battery performance are achieved.
Patent Information
- Application Number
- CN202510065206.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-15
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2045-01-15
AI Technical Summary
The prior art has complex, expensive and difficult to scale the process problems in the surface modification of high-voltage layered oxide positive electrode materials. The differences in properties of various types of layered oxide positive electrode materials lead to poor versatility of the treatment methods and it is difficult to improve the comprehensive electrochemical performance.
After heating the high-pressure laminated oxide positive electrode material sample to 400~1000°C, it is added to a pre-prepared reducing solution for quenching. The mass ratio of the reducing solution to the positive electrode material is controlled to be 1: (0.1~1), and then cooled, filtered, washed and dried to obtain a surface-modified high-pressure laminated oxide positive electrode material.
This method adjusts the surface structure of the positive electrode material through reducing solution quenching method, generates oxygen vacancy and rock salt structure, and achieves surface doping, significantly improves the surface stability of the high-voltage layered oxide positive electrode material and improves the comprehensive electrochemical performance of lithium-ion batteries.
Smart Images

Figure CN119774670A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of new energy technology, and in particular to a method for surface modification of a high-voltage layered oxide positive electrode material. Background Art
[0002] Lithium-ion batteries have the advantages of high energy density, long service life and low cost. The performance of lithium-ion batteries depends largely on their positive electrode materials, which not only store most of the battery's energy but also determine its discharge voltage. Therefore, the development of advanced positive electrode materials is crucial to improving the performance of lithium-ion batteries. Layered oxide positive electrode materials such as lithium cobalt oxide (LCO), high-nickel ternary positive electrode materials (such as NCM811) and lithium-manganese-rich layered positive electrode materials (LLOs) are considered to be the most promising positive electrode material systems in the market due to their advantages in energy density and capacity. In order to meet the requirements for lithium-ion batteries with higher energy density, the specific capacity of the positive electrode material needs to be improved.
[0003] The high voltage of layered oxide cathode materials is crucial to the advancement of high-energy lithium-ion batteries. On the one hand, the upper cutoff potential of lithium cobalt oxide and high nickel ternary cathode materials is increased from 4.3V (vs Li / Li + ) to a high voltage of 4.6V, which can increase its specific capacity and energy density by more than 20-30%; on the other hand, due to the participation of lattice oxygen in charge compensation, the lithium-rich manganese-based hierarchical cathode material can exhibit 250 mAh g at a high upper cutoff potential of 4.6-4.8V. -1 When charged to high potentials, the lattice oxygen of the layered oxide cathode material becomes highly unstable and escapes from the particle surface, resulting in continuous Li / O loss and surface densification. Subsequently, the released oxygen and the unstable high-valent transition metal ions (such as Ni 4+ and Co 4+ ) exacerbate harmful interfacial side reactions, leading to severe electrolyte consumption, the formation of unstable cathode electrolyte interface (CEI), and transition metal dissolution. Therefore, high-energy lithium-ion batteries have a short cycle life and reduced safety performance due to the severe surface instability of high-voltage layered oxide cathode materials.
[0004] At present, the common surface modification methods for high-voltage layered oxide cathode materials include surface coating, electrolyte design and surface structure regulation. The first two ignore the root cause of surface instability, namely, unstable surface structure. In contrast, regulating the surface structure through various surface treatments (such as surface doping and surface reconstruction) has shown great potential in enhancing the surface stability of layered oxide cathodes. For example, high-temperature reducing gas (such as PH3 and NH3, etc.) treatment and wet chemical treatment followed by additional high-temperature calcination usually involve complex, expensive and difficult to scale up processes during their implementation. In addition, the differences in the properties of various types of layered oxide cathode materials make these treatment methods less versatile. Therefore, it is of great significance to develop a simple, cost-effective and universal strategy to regulate the surface structure of high-voltage layered oxide cathodes and improve their comprehensive electrochemical performance.
[0005] Therefore, there is an urgent need for a simple, low-cost and large-scale applicable method for surface modification of high-voltage layered oxide cathode materials. Summary of the invention
[0006] In view of the problem that the existing technology involves complex, expensive and difficult to scale up processes during implementation, and the differences in the properties of various layered oxide positive electrode materials make these treatment methods less universal and difficult to improve the comprehensive electrochemical performance, the present disclosure provides a method for surface modification of high-voltage layered oxide positive electrode materials.
[0007] According to a first aspect of the present invention, there is provided a method for surface modification of a high-voltage layered oxide positive electrode material, comprising: Step a, taking a high-pressure layered oxide positive electrode material sample, heating it to 400-1000° C., and then adding it to a pre-prepared reducing solution for quenching treatment, wherein the mass ratio of the reducing solution to the high-pressure layered oxide positive electrode material sample is controlled to be 1:(0.1-1); Step b: cooling the quenched high-pressure layered oxide positive electrode material sample, filtering, washing and drying the sample to obtain a surface-modified high-pressure layered oxide positive electrode material.
[0008] In some embodiments, the step a further comprises: A reducing solution consisting of an organic aqueous solution with a concentration of 10-500 g / L and an inorganic aqueous solution with a molar concentration of 0.1-3 mol / L is prepared.
[0009] In some embodiments, the organic aqueous solution includes one or more of glucose, acetaldehyde, oxalic acid, urea and ascorbic acid.
[0010] In some embodiments, the inorganic aqueous solution includes one or more of sodium sulfite, sodium bisulfite, ammonium sulfite, ferrous sulfate, sodium nitrite, sodium sulfide, potassium sulfide, sodium borohydride, and sodium ascorbate.
[0011] In some embodiments, step a comprises: Take a high-pressure layered oxide positive electrode material sample, add it into a muffle furnace, heat it to 400~1000°C at a heating rate of 2~8°C / min in an air atmosphere, and then add it to a pre-prepared reducing solution for quenching treatment, wherein the mass ratio of the reducing solution to the high-pressure layered oxide positive electrode material sample is controlled to be 1:(0.1~1).
[0012] In some embodiments, step a further comprises: Take a high-pressure layered oxide positive electrode material sample, add it into a tubular furnace, heat it to 400~1000°C at a heating rate of 2~8°C / min under an oxygen atmosphere, and then add it to a pre-prepared reducing solution for quenching treatment, wherein the mass ratio of the reducing solution to the high-pressure layered oxide positive electrode material sample is controlled to be 1:(0.1~1).
[0013] In some embodiments, step b comprises: The quenched high-pressure layered oxide positive electrode material sample is cooled and filtered, then washed with deionized water and ethanol in succession, and then placed in a vacuum drying oven for drying to obtain a surface-modified high-pressure layered oxide positive electrode material.
[0014] In some embodiments, step b further comprises: The quenched high-pressure layered oxide positive electrode material sample was cooled and filtered, then washed twice with deionized water and then twice with ethanol, and then placed in a vacuum drying oven and dried at 80°C for 6 to 12 hours to obtain a surface-modified high-pressure layered oxide positive electrode material.
[0015] In some embodiments, the high-voltage layered oxide positive electrode material includes a lithium cobalt oxide positive electrode material, a high-nickel ternary positive electrode material, and a lithium-manganese-rich layered positive electrode material.
[0016] In some embodiments, the molecular formula of the lithium-rich manganese-based layered positive electrode material is Li 1+x TM 1-x O2, wherein the TM is at least two of Ni, Co and Mn, and the value of x is 0 <x<1。
[0017] The above-mentioned method for surface modification of a high-pressure layered oxide positive electrode material comprises taking a high-pressure layered oxide positive electrode material sample, heating it to 400-1000°C, and then adding it to a pre-prepared reducing solution for quenching treatment, wherein the mass ratio of the reducing solution to the high-pressure layered oxide positive electrode material sample is controlled to be 1: (0.1-1), and the high-pressure layered oxide positive electrode material sample after quenching treatment is cooled, filtered, washed and dried to obtain a surface-modified high-pressure layered oxide positive electrode material. The present invention provides a method for surface modification of a high-pressure layered oxide positive electrode material, wherein the surface structure of the high-pressure layered oxide positive electrode is adjusted by a reducing solution quenching method, oxygen vacancies and rock salt structures are generated on the particle surface, surface doping is achieved, and the surface stability of the high-pressure layered oxide positive electrode material is improved. In the above-mentioned process, the liquid-solid interface reaction, the layered oxide positive electrode material and the reducing solution are fully and uniformly contacted and reacted, so that the surface structure is completely and uniformly regulated, and the comprehensive electrochemical performance (first coulomb efficiency, high-voltage cycle stability) of the lithium-ion battery can be significantly improved. The above-mentioned processing steps are simple and time-saving, the reaction conditions are easy to control, and are suitable for industrial continuous production, which improves the production efficiency and is suitable for large-scale production. The reducing solvents used are all common chemical raw materials with low prices and low production costs. It has wide applicability in solving the surface instability of battery positive electrode materials, and can even be extended to the surface modification of lithium-ion battery positive electrode materials such as high-voltage spinel and other sodium-ion battery layered oxide positive electrode materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings in the following description are only some embodiments of the present invention. For ordinary technicians in this field, other embodiments can be obtained based on these drawings without paying creative work.
[0019] Figure 1 A flow chart of a method for surface modification of a high-voltage layered oxide positive electrode material provided in one embodiment of the present invention; Figure 2 A scanning electron microscope (SEM) morphology image of the surface-modified lithium-rich manganese-based layered positive electrode material obtained in accordance with Example 5 provided by the present invention; Figure 3 A high-angle annular dark field scanning transmission (HAADF-STEM) image of the particle surface area of the surface-modified lithium-rich manganese-based layered positive electrode material obtained in accordance with Example 5 provided by the present invention; Figure 4 The original lithium-rich manganese-based layered positive electrode material Li that has not been treated by the reducing solution quenching method in the blank example provided by the present invention is 1.2Ni 0.2 Mn 0.6 Scanning electron microscope (SEM) morphology of O2; Figure 5 The original lithium-rich manganese-based layered positive electrode material Li that has not been treated by the reducing solution quenching method in the blank example provided by the present invention is 1.2 Ni 0.2 Mn 0.6 High-angle annular dark field scanning transmission (HAADF-STEM) image of the surface area of O2 particles; Figure 6 Schematic diagram of X-ray diffraction (XRD) patterns of Examples 5-6 and a blank example (original lithium-rich manganese-based laminated positive electrode material) provided by the present invention; Figure 7 The cycle performance diagram of Examples 1-2, a blank example (lithium cobalt oxide) and a comparative example 1 provided by the present invention at a 1C rate; Figure 8 Cycling performance diagrams of Examples 3-4, a blank example (high nickel ternary positive electrode material NCM811) and Comparative Example 2 provided by the present invention at a 1C rate; Fig. 9 A comparison chart of the first charge and discharge curves of Examples 5-7, a blank example (lithium-rich manganese-based layered positive electrode material) and Comparative Example 3 provided by the present invention at a rate of 0.1C; Fig.10 The cycling performance diagram of Examples 5-7, a blank example (lithium-rich manganese-based layered positive electrode material) and Comparative Example 3 provided by the present invention at a 1C rate. DETAILED DESCRIPTION
[0020] The following is a further detailed description of the embodiments of the present disclosure in conjunction with the accompanying drawings and examples. The detailed description of the following embodiments and the accompanying drawings are used to exemplarily illustrate the principles of the present disclosure, but cannot be used to limit the scope of the present disclosure. The present disclosure can be implemented in many different forms and is not limited to the specific embodiments disclosed herein, but includes all technical solutions that fall within the scope of the claims.
[0021] The present disclosure provides these embodiments to make the present disclosure thorough and complete, and to fully express the scope of the present disclosure to those skilled in the art. It should be noted that unless otherwise specifically stated, the relative arrangement of the parts and steps, the composition of the materials, the numerical expressions and the numerical values set forth in these embodiments should be interpreted as being merely exemplary, and not as limiting.
[0022] It should be noted that, in the description of the present disclosure, unless otherwise specified, the meaning of "multiple" is greater than or equal to two; the terms "upper", "lower", "left", "right", "inner", "outer", etc., indicating the orientation or positional relationship, are only for the convenience of describing the present disclosure and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation of the present disclosure. When the absolute position of the object being described changes, the relative positional relationship may also change accordingly.
[0023] In addition, the words "first", "second" and similar words used in this disclosure do not indicate any order, quantity or importance, but are only used to distinguish different parts. The words "include" or "comprise" and similar words mean that the elements before the word include the elements listed after the word, and do not exclude the possibility of including other elements.
[0024] It should also be noted that in the description of the present disclosure, unless otherwise clearly specified and limited, the terms "installed", "connected", and "connected" should be understood in a broad sense. For example, it can be a fixed connection, a detachable connection, or an integral connection; it can be directly connected or indirectly connected through an intermediate medium. For ordinary technicians in this field, the specific meanings of the above terms in the present disclosure can be understood according to the specific circumstances. When a specific device is described as being located between a first device and a second device, there may or may not be an intermediate device between the specific device and the first device or the second device.
[0025] All terms used in the present disclosure have the same meanings as those understood by those of ordinary skill in the art to which the present disclosure belongs, unless otherwise specifically defined. It should also be understood that terms defined in general dictionaries, for example, should be interpreted as having meanings consistent with their meanings in the context of the relevant technology, and should not be interpreted in an idealized or extremely formal sense, unless explicitly defined as such herein.
[0026] Technologies, methods, and equipment known to ordinary technicians in the relevant art may not be discussed in detail, but where appropriate, the technologies, methods, and equipment should be considered part of the specification.
[0027] It should be understood that the embodiments of the present invention shown in the exemplary embodiments are only illustrative. Although only a few embodiments are described in detail in the present invention, it is easy for those skilled in the art to appreciate that multiple modifications are feasible without actually departing from the teaching of the subject matter of the present invention. Accordingly, all such modifications should be included within the scope of the present invention. Without departing from the gist of the present invention, other replacements, modifications, changes and deletions may be made to the design, operating conditions and parameters of the following exemplary embodiments.
[0028] Please refer to Figure 1 , Figure 1 The flowchart of a method for surface modification of a high-voltage layered oxide positive electrode material provided by one embodiment of the present invention is shown. A method 100 for surface modification of a high-voltage layered oxide positive electrode material comprises: Step a, taking a high-pressure layered oxide positive electrode material sample, heating it to 400-1000° C., and then adding it to a pre-prepared reducing solution for quenching treatment, wherein the mass ratio of the reducing solution to the high-pressure layered oxide positive electrode material sample is controlled to be 1:(0.1-1); Specifically, quenching is a common heat treatment process in the steel production process, which is extended to the preparation and modification of various functional materials.
[0029] Specifically, the pre-prepared reducing solution includes an aqueous solution of an organic substance having an aldehyde group / unsaturated bond and an aqueous solution of an inorganic substance / organic salt containing a low-valent element, wherein the aqueous solution of an organic substance having an aldehyde group / unsaturated bond includes glucose, acetaldehyde, oxalic acid, urea and ascorbic acid, etc., and the aqueous solution of an inorganic substance / organic salt containing a low-valent element includes sodium sulfite, sodium bisulfite, ammonium sulfite, ferrous sulfate, sodium nitrite, sodium sulfide, potassium sulfide, sodium borohydride, sodium ascorbate, etc. These reducing solutions are all common chemical raw materials, low in price, and low in production cost.
[0030] Specifically, the concentration of the organic aqueous solution in the pre-prepared reducing solution is 10-500 g / L, and the molar concentration of the inorganic aqueous solution is 0.1-3 mol / L.
[0031] Specifically, oxygen vacancies and rock salt structures are generated on the surface of high-pressure layered oxide cathode material particles by reducing solution quenching method, and surface doping is achieved, which improves the surface stability of high-pressure layered oxide cathode material under high pressure. Among them, surface oxygen vacancies can not only promote the surface area Li + Diffusion can also inhibit the irreversible release of lattice oxygen; the surface rock salt structure shell has excellent chemical and electrochemical stability, which can significantly inhibit the release of lattice oxygen, the dissolution of transition metal ions and interfacial side reactions, and improve the interface stability; surface ion doping can also regulate the electronic structure of the material, which can inhibit the damage of the material's crystal structure, the surface irreversible phase change and the release of lattice oxygen.
[0032] Step b: cooling the quenched high-pressure layered oxide positive electrode material sample, filtering, washing and drying the sample to obtain a surface-modified high-pressure layered oxide positive electrode material.
[0033] The surface structure of high-voltage layered oxide cathode materials is regulated by the reducing solution quenching method, and the residual heat carried by the particles is used to generate Li / M n+ Ion exchange reaction (Mn+ Some cations present in reducing solutions, such as H + 、Na + , Fe 3+ The surface of the particles is doped with oxygen vacancies and rock salt structures through the reduction reaction of the layered oxide cathode material (such as ions, etc.) and transition metal ions, and the surface reconstruction layer can be precisely controlled by changing the temperature of the layered oxide cathode material, the type and concentration of the reducing solution, etc. The prepared surface-modified high-voltage layered oxide cathode material has higher first coulombic efficiency and discharge specific capacity, better high-voltage cycle stability, and inhibits lattice oxygen release and transition metal ion dissolution compared to the original layered oxide cathode material.
[0034] The above-mentioned method for surface modification of high-voltage layered oxide cathode materials adjusts the surface structure of the high-voltage layered oxide cathode by quenching with a reducing solution, generates oxygen vacancies and rock salt structures on the particle surface, realizes surface doping, and improves the surface stability of the high-voltage layered oxide cathode material. In the above process, the liquid-solid interface reaction, the layered oxide cathode material and the reducing solution fully and evenly contact and react, so that the surface structure is completely and evenly regulated, and the comprehensive electrochemical performance (first coulomb efficiency, high-voltage cycle stability) of the lithium-ion battery can be significantly improved.
[0035] The above-mentioned processing steps are simple and time-saving, the reaction conditions are easy to control, and are suitable for industrial continuous production. They improve production efficiency and are suitable for large-scale production. They are widely applicable in solving the surface instability of battery positive electrode materials, and can even be extended to the surface modification of lithium-ion battery positive electrode materials such as high-voltage spinel and other sodium-ion battery layered oxide positive electrode materials.
[0036] According to some embodiments of the present invention, before step a, the method further includes: preparing a reducing solution composed of an organic aqueous solution with a concentration of 10 to 500 g / L and an inorganic aqueous solution with a molar concentration of 0.1 to 3 mol / L. By rationally controlling the concentration of the organic aqueous solution and the concentration of the inorganic aqueous solution, a reducing solution that meets the requirements of the reducing solution quenching method can be accurately prepared, which is conducive to the subsequent generation of oxygen vacancies and rock salt structures on the surface of the high-pressure layered oxide positive electrode material particles and the realization of surface doping, thereby improving the surface stability of the high-pressure layered oxide positive electrode material under high pressure.
[0037] According to some embodiments of the present invention, the organic aqueous solution includes one or more of glucose, acetaldehyde, oxalic acid, urea and ascorbic acid. The above-mentioned glucose, acetaldehyde, oxalic acid, urea and ascorbic acid are all commonly used industrial raw materials, easy to obtain and low in cost, and suitable for industrial continuous production.
[0038] According to some embodiments of the present invention, the inorganic aqueous solution includes one or more of sodium sulfite, sodium bisulfite, ammonium sulfite, ferrous sulfate, sodium nitrite, sodium sulfide, potassium sulfide, sodium borohydride, and sodium ascorbate. The above-mentioned sodium sulfite, sodium bisulfite, ammonium sulfite, ferrous sulfate, sodium nitrite, sodium sulfide, potassium sulfide, sodium borohydride, sodium ascorbate, etc. are all commonly used industrial raw materials, easy to obtain and low in cost, and suitable for industrial continuous production.
[0039] According to several embodiments of the present invention, step a comprises: taking a high-pressure layered oxide positive electrode material sample, adding it into a muffle furnace, heating it to 400-1000°C at a heating rate of 2-8°C / min in an air atmosphere, and then adding it into a pre-prepared reducing solution for quenching treatment, wherein the mass ratio of the reducing solution to the high-pressure layered oxide positive electrode material sample is controlled to be 1:(0.1-1). Optionally, the high-pressure layered oxide positive electrode material sample is added into a muffle furnace, heated by the air atmosphere in the muffle furnace, and then added into a pre-prepared reducing solution for quenching treatment after being heated to a preset temperature range, and the mass ratio of the reducing solution to the high-pressure layered oxide positive electrode material sample is controlled to be maintained at 1:(0.1-1), so that the reducing quenching treatment can be carried out to the greatest extent, the layered oxide positive electrode material and the reducing solution are fully and uniformly contacted and reacted, so that the surface structure is completely and uniformly regulated, and the comprehensive electrochemical performance (first coulomb efficiency, high-voltage cycle stability) of the lithium-ion battery can be significantly improved.
[0040] According to some embodiments of the present invention, step a further comprises: taking a high-pressure layered oxide positive electrode material sample, adding it into a tubular furnace, heating it to 400-1000°C at a heating rate of 2-8°C / min under an oxygen atmosphere, and then adding it into a pre-prepared reducing solution for quenching treatment, wherein the mass ratio of the reducing solution to the high-pressure layered oxide positive electrode material sample is controlled to be 1:(0.1-1). Optionally, the high-pressure layered oxide positive electrode material sample is added into a tubular furnace, heated by the oxygen atmosphere in the tubular furnace, and then added into a pre-prepared reducing solution for quenching treatment after being heated to a preset temperature range, and the mass ratio of the reducing solution to the high-pressure layered oxide positive electrode material sample is controlled to be maintained at 1:(0.1-1), so that the reducing quenching treatment can be carried out to the greatest extent, the layered oxide positive electrode material and the reducing solution are fully and uniformly contacted and reacted, so that the surface structure is completely and uniformly regulated, and the comprehensive electrochemical performance (first coulomb efficiency, high-voltage cycle stability) of the lithium-ion battery can be significantly improved.
[0041] According to some embodiments of the present invention, step b includes: cooling and filtering the quenched high-pressure layered oxide positive electrode material sample, then washing it with deionized water and ethanol, and then placing it in a vacuum drying oven for drying to obtain a surface-modified high-pressure layered oxide positive electrode material. Washing it with deionized water and ethanol can ensure sufficient cleaning and minimize the impact of surface impurities on the subsequent surface modification process.
[0042] According to some embodiments of the present invention, step b further comprises: cooling and filtering the quenched high-pressure layered oxide cathode material sample, washing it twice with deionized water and then washing it twice with ethanol, and then placing it in a vacuum drying oven and drying it at 80°C for 6-12 hours to obtain a surface-modified high-pressure layered oxide cathode material. The number of times of washing with deionized water and ethanol is reasonably controlled to reduce resource waste while ensuring sufficient washing, and at the same time, the drying time after washing is reasonably controlled to fully dry the surface-modified high-pressure layered oxide cathode material.
[0043] According to some embodiments of the present invention, the high-voltage layered oxide positive electrode material includes a lithium cobalt oxide positive electrode material, a high-nickel ternary positive electrode material, and a lithium-manganese-rich layered positive electrode material.
[0044] According to some embodiments of the present invention, the molecular formula of the lithium-rich manganese-based layered positive electrode material is Li 1+x TM 1-x O2, where TM is at least two of Ni, Co and Mn, and x is 0 <x<1。
[0045] In order to further understand the method for surface modification of a high-voltage layered oxide positive electrode material of the present invention, it is further described in detail in the following specific examples.
[0046] Example 1 Prepare a glucose solution with a concentration of 100 g / L, put the original lithium cobalt oxide positive electrode material into a muffle furnace, and heat it to 1000°C at a heating rate of 5°C / min; then pour it directly into the glucose solution for quenching, and control the mass ratio of glucose solution to lithium cobalt oxide to be 1:0.3. Wait for the lithium cobalt oxide to cool completely, filter and wash, wash it with deionized water twice, and then wash it with ethanol twice, and dry it in a vacuum drying oven at a temperature below 80°C for 12 hours to obtain a surface-modified high-pressure lithium cobalt oxide positive electrode material. In this embodiment, the original lithium cobalt oxide positive electrode material is a commercially available single crystal lithium cobalt oxide with a size of about 10μm, which is prepared by an existing solid phase method and will not be repeated.
[0047] Example 2 Prepare a sodium sulfite solution with a concentration of 2 mol / L, put the original lithium cobalt oxide positive electrode material into a muffle furnace, and heat it to 1000°C at a heating rate of 5°C / min; then pour it directly into the sodium sulfite solution for quenching, and control the mass ratio of the sodium sulfite solution to the lithium cobalt oxide to be 1:0.1. Wait for the lithium cobalt oxide to cool completely before filtering and washing, first wash it with deionized water twice, then wash it with ethanol twice, and then dry it in a vacuum drying oven at a temperature below 80°C for 12 hours to obtain a surface-modified high-pressure lithium cobalt oxide positive electrode material. Among them, the original lithium cobalt oxide positive electrode material used in Example 2 is the same as that in Example 1, and will not be repeated.
[0048] Example 3 Prepare a 100g / L urea solution and mix the original high-nickel ternary cathode material NCM811 (LiNi 0.8 Mn 0.1 Co 0.1 O2) was placed in a tubular furnace and heated to 700°C at a heating rate of 5°C / min under an oxygen flow atmosphere (flow rate of 100mL / min); then it was directly poured into a urea solution for quenching, and the mass ratio of urea solution to NCM811 was 1:1. After waiting for NCM811 to cool completely, it was filtered and washed, first washed with deionized water twice, then washed with ethanol twice, and then dried in a vacuum drying oven at 80°C for 12 hours to obtain a surface-modified high-pressure NCM811 positive electrode material. Among them, the original NCM811 used in Example 2 is a commercially available polycrystalline high-nickel ternary positive electrode material, which is prepared by the existing co-precipitation method and will not be repeated.
[0049] Example 4 A sodium ascorbate solution with a concentration of 2 mol / L was prepared and the original high-nickel ternary cathode material NCM811 (LiNi 0.8 Mn 0.1 Co 0.1 O2) was placed in a tube furnace and heated to 700°C at a heating rate of 5°C / min under an oxygen flow atmosphere (flow rate of 100 mL / min); then it was directly poured into a sodium ascorbate solution for quenching, and the mass ratio of the sodium ascorbate solution to the NCM811 positive electrode material was 1:0.2. After the NCM811 was completely cooled, it was filtered and washed, first washed twice with deionized water, and then washed twice with ethanol, and then dried in a vacuum drying oven at 80°C for 12 hours to obtain a surface-modified high-pressure NCM811 positive electrode material. Among them, the original NCM811 used in Example 4 is the same as that in Example 3, and will not be repeated.
[0050] Example 5 Prepare a glucose solution with a concentration of 100 g / L and mix the original lithium-rich manganese-based layered cathode material Li 1.2 Ni 0.2 Mn 0.6 O2 is placed in a muffle furnace and heated to 900°C at a heating rate of 5°C / min; it is then directly poured into a glucose solution for quenching, and the mass ratio of the glucose solution to the lithium-rich manganese-based positive electrode material is 1:0.3. After the lithium-rich manganese-based positive electrode material is completely cooled, it is filtered and washed, washed twice with deionized water, washed twice with ethanol, and dried in a vacuum drying oven at 80°C for 12 hours to obtain a surface-modified high-voltage lithium-rich manganese-based positive electrode material. The lithium-rich manganese-based positive electrode material Li in Example 5 1.2 Ni 0.2 Mn 0.6 O2 was prepared by the sol-gel method in the laboratory, and the particles were single crystal particles with a diameter of about 300 nm. The preparation process is a prior art and will not be described in detail. The scanning electron microscope (SEM) morphology of the surface-modified lithium-rich manganese-based positive electrode material obtained in Example 5 is shown in FIG. Figure 2 As shown, the high-angle annular dark field scanning transmission (HAADF-STEM) image of the particle surface area of the surface-modified lithium-rich manganese-based layered positive electrode material obtained in Example 5 is as follows Figure 3 shown.
[0051] Example 6 A 1 mol / L ferrous sulfate solution was prepared and the original lithium-rich manganese-based layered cathode material Li 1.2 Ni 0.2 Mn 0.6 O2 is placed in a muffle furnace and heated to 900°C at a heating rate of 5°C / min; it is then directly poured into a ferrous sulfate solution for quenching, and the mass ratio of the ferrous sulfate solution to the lithium-rich manganese-based layered positive electrode material is 1:0.1. After the lithium-rich manganese-based layered positive electrode material is completely cooled, it is filtered and washed, first washed twice with deionized water, then washed twice with ethanol, and then dried in a vacuum drying oven at 80°C for 12 hours to obtain a surface-modified lithium-rich manganese-based layered positive electrode material. Among them, the original lithium-rich manganese-based layered positive electrode material used in Example 6 is the same as that in Example 5, and will not be repeated.
[0052] Example 7 Prepare a sodium borohydride solution with a concentration of 2 mol / L and mix the original lithium-rich manganese-based layered cathode material Li 1.2 Ni 0.2 Mn 0.6O2 is placed in a muffle furnace and heated to 900°C at a heating rate of 5°C / min; it is then directly poured into a sodium borohydride solution for quenching, and the mass ratio of the sodium borohydride solution to the lithium-rich manganese-based layered positive electrode material is 1:1. After the material is completely cooled, it is filtered and washed, first washed twice with deionized water, then washed twice with ethanol, and dried in a vacuum drying oven at 80°C for 12 hours to obtain a surface-modified lithium-rich manganese-based layered positive electrode material. Among them, the original lithium-rich manganese-based layered positive electrode material used in Example 7 is the same as that in Example 5, and will not be repeated.
[0053] Blank example The original lithium cobalt oxide, the original high nickel ternary cathode material NCM811 and the original lithium-rich manganese-based cathode material Li that have not been treated by the reducing solution quenching method 1.2 Ni 0.2 Mn 0.6 O2. Among them, the original lithium-rich manganese-based layered positive electrode material Li that has not been treated by the reducing solution quenching method 1.2 Ni 0.2 Mn 0.6 The scanning electron microscope (SEM) morphology of O2 is shown in Figure 4 As shown, the original lithium-rich manganese-based layered cathode material Li without the reduction solution quenching method 1.2 Ni 0.2 Mn 0.6 High-angle annular dark field scanning transmission (HAADF-STEM) images of the surface area of O2 particles are shown in Figure 2. Figure 5 shown.
[0054] Depend on Figure 2 and Figure 4 By comparison, it can be seen that the lithium-rich manganese-based layered positive electrode materials in Example 5 and Blank Example 3 are both nanoparticles prepared by the sol-gel method, with a size of about 300 nm. At the same time, the surface of Example 5 is rougher, which may be due to the surface structure regulation caused by the quenching process. Figure 5 It can be seen that the original lithium-rich manganese-based layered cathode material Li 1.2 Ni 0.2 Mn 0.6 The surface area of O2 is a well-layered structure. Figure 5 and Figure 3 By comparison, it can be seen that a rock-salt shell with a thickness of about 4 nm appears on the surface of the lithium-rich manganese-based layered positive electrode material in Example 5, and the internal layered structure is still well maintained. This phenomenon indicates that the Li / M n+Ion exchange reactions and reduction reactions of transition metal ions induce the production of a protective rock salt structure shell, inhibiting interfacial side reactions and lattice oxygen release, thereby achieving excellent high-pressure cycling stability.
[0055] Comparative Example 1 Comparative Example 1 is compared with Examples 1-2. In Comparative Example 1, deionized water (not containing any reducing substances) is used as the quenching solution.
[0056] Comparative Example 2 Comparative Example 2 is compared with Examples 3-4. In Comparative Example 2, deionized water (not containing any reducing substances) is used as the quenching solution.
[0057] Comparative Example 3 Comparative Example 3 is compared with Examples 5-7. In Comparative Example 3, deionized water (not containing any reducing substances) is used as the quenching solution.
[0058] Among them, the X-ray diffraction (XRD) patterns of Examples 5-6, Comparative Example 1 and the blank example (original lithium-rich manganese-based layered positive electrode material) are as follows: Figure 6 As shown, from Figure 6 It can be seen that the lithium-rich manganese-based layered positive electrode materials in Example 5, Example 6 and Blank Example 3 all show similar XRD patterns, and no other additional diffraction peaks appear, indicating that the reducing solution quenching process will not affect the crystal structure of the lithium-rich layered manganese-based positive electrode material.
[0059] The cycle performance of Example 1-2, Blank Example (lithium cobalt oxide) and Comparative Example 1 at 1C rate is shown in the figure below: Figure 7 As shown, from Figure 7 It can be seen that compared with the blank example, Example 1 and Example 2 can obtain a higher capacity retention rate, which is due to the surface modification of the material (including: surface oxygen vacancies, rock salt structure shell and surface doping) achieved by quenching with a reducing solution, which inhibits the electrolyte decomposition under high pressure, irreversible transformation of the surface structure and dissolution of transition metals and other interface side reactions. In Comparative Example 1, since there is no reducing substance involved in quenching, the degree of surface structure regulation is small, and the material surface is more damaged by water, so its specific capacity is the lowest and the cycle performance is poor.
[0060] The cycle performance of Examples 3-4, Blank Example (high nickel ternary positive electrode material NCM811) and Comparative Example 2 at 1C rate is shown in the figure below: Figure 8 As shown, from Figure 8It can be seen that compared with the blank example, Example 3 and Example 4 have the highest capacity retention rate, which is due to the surface modification of the material (including surface oxygen vacancies, rock salt structure shell and surface doping) achieved by quenching with a reducing solution, which inhibits the electrolyte decomposition under high pressure, irreversible transformation of the surface structure and dissolution of transition metals and other interface side reactions. In Comparative Example 2, since there is no reducing substance involved in quenching, the degree of surface structure regulation is small, but the deionized water quenching process and the subsequent washing process will partially remove the residual alkali on its surface, and also partially alleviate the interface side reactions, so its cycle stability is slightly better than the blank example, but still far worse than Example 3 and Example 4.
[0061] The comparison of the first charge and discharge curves of Examples 5-7, Blank Example (lithium-rich manganese-based layered positive electrode material) and Comparative Example 3 at a rate of 0.1C is shown in the figure below: Fig. 9 As shown, from Fig. 9 It can be seen that compared with the blank example and comparative example 3, Examples 5-7 can obtain higher first coulombic efficiency and discharge specific capacity. This is due to the surface modification of the material (including surface oxygen vacancies, rock salt structure shell and surface doping), which can inhibit the lattice oxygen release and interfacial side reactions of the lithium-manganese-rich layered positive electrode material and improve the reversibility of the oxygen redox process.
[0062] The cycle performance of Examples 5-7, Blank Example (lithium-rich manganese-based layered positive electrode material) and Comparative Example 3 at 1C rate is shown in the figure below: Fig.10 As shown, from Fig.10 It can be seen that compared with the blank example and comparative example 3, Examples 5-7 exhibit the best capacity retention rate and the smallest voltage decay rate. This is because in subsequent cycles, the stable surface structure can significantly alleviate problems such as electrolyte decomposition, lattice oxygen release, irreversible phase change from layered to spinel, and transition metal dissolution, thereby improving the capacity retention rate and voltage retention rate.
[0063] The high-voltage layered oxide positive electrode materials obtained in the above Examples 1-7, the blank examples and the comparative examples 1-3 were mixed with a conductive agent (conductive carbon black super-P) and a binder (polyvinylidene fluoride, PVDF) at a mass ratio of 8:1:1 at room temperature in N-methylpyrrolidone (NMP), and then uniformly coated on an aluminum current collector, with an active material surface loading of 2.5-6.0 mg cm -2, then dried, cut, rolled, and transferred to a glove box for storage. CR2032 button cells were assembled in an argon-filled glove box. The negative electrode was a metal lithium sheet, the separator was a Celgard2400 separator, and the electrolyte was 1.0 M LiPF6 dissolved in a mixture of EC:DMC:EMC. The mass fraction ratio of the three solvents was 1:1:1 wt%. The button cell was first activated at a current density of 0.1C (for lithium cobalt oxide / high nickel ternary positive electrode materials, 1C=200mA / g; for lithium-rich manganese-based laminated positive electrode materials, 1C=250mA / g). After activation, the charge and discharge cycle was carried out at a current density of 1C. The test voltage ranges were 3.0-4.5V for lithium cobalt oxide, 2.8-4.5V for high nickel ternary positive electrode materials, and 2.0-4.8V for lithium-rich manganese-based laminated positive electrode materials.
[0064] Finally, the test results of the initial capacity, capacity after cycle and capacity retention rate corresponding to Examples 1-2, the blank example and Comparative Example 1 are shown in Table 1 below: Table 1
[0065] As can be seen from Table 1, compared with the blank example, Example 1 and Example 2 can obtain higher first coulombic efficiency and capacity retention rate, but the first discharge capacity is almost the same, which is due to the surface modification of the material (including surface oxygen vacancies, rock salt structure shell and surface doping) achieved by quenching with a reducing solution, which inhibits the electrolyte decomposition under high pressure, irreversible transformation of the surface structure and dissolution of transition metals and other interface side reactions. In Comparative Example 1, since there is no reducing substance involved in quenching, the degree of surface structure regulation is small, and the material surface is more damaged by water, so its specific capacity is the lowest and the cycle performance is poor.
[0066] The test results of the initial capacity, capacity after cycle and capacity retention rate corresponding to Examples 3-4, Blank Example and Comparative Example 2 are shown in Table 2 below: Table 2
[0067] As can be seen from Table 2, compared with the blank example, Example 3 and Example 4 can obtain higher first coulombic efficiency and capacity retention rate, but the first discharge capacity is almost the same, which is due to the surface modification of the material (including surface oxygen vacancies, rock salt structure shell and surface doping) achieved by quenching with a reducing solution, which inhibits the electrolyte decomposition under high pressure, irreversible transformation of the surface structure and dissolution of transition metals and other interface side reactions. In Comparative Example 2, since there is no reducing substance involved in quenching, the degree of surface structure regulation is small, but the deionized water quenching process and the subsequent washing process will partially remove the residual alkali on its surface, and also partially alleviate the interface side reactions, so its first coulombic efficiency and cycle stability are better than the blank example, but still far worse than Example 3 and Example 4.
[0068] The test results of the initial capacity, capacity after cycle and capacity retention rate corresponding to Examples 5-7, the blank example and Comparative Example 3 are shown in Table 3 below: Table 3
[0069] As can be seen from Table 3, compared with the blank example and comparative example 3, Examples 5-7 can obtain higher first coulombic efficiency and discharge specific capacity, which is due to the surface modification of the material (including surface oxygen vacancies, rock salt structure shell and surface doping), which can inhibit the lattice oxygen release and interface side reactions of the lithium-rich manganese-based layered positive electrode material and improve the reversibility of the oxygen redox process; in subsequent cycles, thanks to its stable surface structure, problems such as electrolyte decomposition, lattice oxygen release, irreversible phase change from layered to spinel, and transition metal dissolution are significantly alleviated, resulting in Examples 5-7 showing the best capacity retention rate and the smallest voltage decay rate.
[0070] From the measurement results in the above Examples 1-7, Comparative Examples 1-3 and Blank Examples, it can be seen that the surface structure of the high-pressure layered oxide positive electrode is adjusted by the reducing solution quenching method, oxygen vacancies and rock salt structures are generated on the particle surface, surface doping is achieved, and the surface stability of the high-pressure layered oxide positive electrode material is improved. Among them, the liquid-solid interface reaction in the above process, the layered oxide positive electrode material and the reducing solution are fully and uniformly contacted and reacted, so that the regulation of the surface structure is complete and uniform, and the comprehensive electrochemical performance (first coulomb efficiency, high-voltage cycle stability) of the lithium-ion battery can be significantly improved. The entire processing step is simple and time-saving, the reaction conditions are easy to control, it is suitable for industrial continuous production, the production efficiency is improved and it is suitable for large-scale production, it has wide applicability in solving the surface instability of battery positive electrode materials, and can even be extended to the surface modification of lithium-ion battery positive electrode materials such as high-voltage spinel and other sodium-ion battery layered oxide positive electrode materials.
[0071] So far, various embodiments of the present disclosure have been described in detail. In order to avoid obscuring the concept of the present disclosure, some details known in the art are not described. Based on the above description, those skilled in the art can fully understand how to implement the technical solution disclosed here.
[0072] Although some specific embodiments of the present disclosure have been described in detail by way of examples, it should be understood by those skilled in the art that the above examples are for illustration only and are not intended to limit the scope of the present disclosure. It should be understood by those skilled in the art that the above embodiments may be modified or some technical features may be replaced by equivalents without departing from the scope and spirit of the present disclosure. In particular, the various technical features mentioned in the various embodiments may be combined in any manner as long as there is no structural conflict.
Claims
1. A method for surface modification of a high-voltage layered oxide positive electrode material, characterized in that: include: Step a, taking a high-pressure layered oxide positive electrode material sample, heating it to 400-1000° C., and then adding it to a pre-prepared reducing solution for quenching treatment, wherein the mass ratio of the reducing solution to the high-pressure layered oxide positive electrode material sample is controlled to be 1:(0.1-1); Step b: cooling the quenched high-pressure layered oxide positive electrode material sample, filtering, washing and drying the sample to obtain a surface-modified high-pressure layered oxide positive electrode material.
2. The method for surface modification of high-voltage layered oxide positive electrode materials according to claim 1, characterized in that: The step a also includes: A reducing solution consisting of an organic aqueous solution with a concentration of 10-500 g / L and an inorganic aqueous solution with a molar concentration of 0.1-3 mol / L is prepared.
3. The method for surface modification of high-voltage layered oxide positive electrode materials according to claim 2, characterized in that: The organic aqueous solution includes one or more of glucose, acetaldehyde, oxalic acid, urea and ascorbic acid.
4. The method for surface modification of high-voltage layered oxide positive electrode materials according to claim 2, characterized in that: The inorganic aqueous solution includes one or more of sodium sulfite, sodium bisulfite, ammonium sulfite, ferrous sulfate, sodium nitrite, sodium sulfide, potassium sulfide, sodium borohydride, and sodium ascorbate.
5. The method for surface modification of high-voltage layered oxide positive electrode materials according to claim 1, characterized in that: The step a comprises: Take a high-pressure layered oxide positive electrode material sample, add it into a muffle furnace, heat it to 400~1000°C at a heating rate of 2~8°C / min in an air atmosphere, and then add it to a pre-prepared reducing solution for quenching treatment, wherein the mass ratio of the reducing solution to the high-pressure layered oxide positive electrode material sample is controlled to be 1:(0.1~1).
6. The method for surface modification of high-voltage layered oxide positive electrode materials according to claim 1, characterized in that: The step a also includes: Take a high-pressure layered oxide positive electrode material sample, add it into a tubular furnace, heat it to 400~1000°C at a heating rate of 2~8°C / min under an oxygen atmosphere, and then add it to a pre-prepared reducing solution for quenching treatment, wherein the mass ratio of the reducing solution to the high-pressure layered oxide positive electrode material sample is controlled to be 1:(0.1~1).
7. The method for surface modification of high-voltage layered oxide positive electrode materials according to claim 1, characterized in that: The step b comprises: The quenched high-pressure layered oxide positive electrode material sample is cooled and filtered, then washed with deionized water and ethanol in succession, and then placed in a vacuum drying oven for drying to obtain a surface-modified high-pressure layered oxide positive electrode material.
8. The method for surface modification of high-voltage layered oxide positive electrode materials according to claim 7, characterized in that: The step b also includes: The quenched high-pressure layered oxide positive electrode material sample was cooled and filtered, then washed twice with deionized water and then twice with ethanol, and then placed in a vacuum drying oven and dried at 80°C for 6 to 12 hours to obtain a surface-modified high-pressure layered oxide positive electrode material.
9. The method for surface modification of high-voltage layered oxide positive electrode materials according to claim 1, characterized in that: The high-voltage layered oxide positive electrode material includes a lithium cobalt oxide positive electrode material, a high-nickel ternary positive electrode material, and a lithium-manganese-rich layered positive electrode material.
10. The method for surface modification of high-voltage layered oxide positive electrode materials according to claim 9, characterized in that: The molecular formula of the lithium-rich manganese-based positive electrode material is Li 1+x TM 1-x O2, wherein the TM is at least two of Ni, Co and Mn, and the value of x is 0 <x<1。
Citation Information
Patent Citations
Method for preparing oxygen vacancy lithium-rich manganese-based layered positive electrode material through solid-liquid method
CN110828816A
Surface modified battery material, preparation method thereof and battery
CN115548337A
Production of lithium-manganese oxide by quenching method
JP1998330118A